VD_FINDINFO HC / 2013 / 557 vom 5. September 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS | 109 al. 1 CPC (CH), 122 al. 1 let. a CPC (CH), 123 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)